Therapeutic Management of Snake Bite in a Rottweiler Dog - Bharai, MJ; Dodiya, PG; Vagh, AA (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
M Snakebite cases are more common in horses and dogs when compared to other animals such as cattle, sheep, and goats. Snake envenomation can be difficult to diagnose if the incident was not witnessed. Clinical signs may vary greatly depending on the species of snake involved, and the quantity and toxicity of the venom injected. Dogs are commonly presented with extensive edematous swelling, severe pain, ecchymosis, and discoloration of the skin in the affected area within several hours after the bite (Garg, 2002) The animals exhibit various symptoms like cardio-pulmonary dysfunction, local tissue damage, blood coagulation defects, ataxia etc, depending on type of snake bite (Bhardwaj, 2011). Systemic signs can vary and may include hypotension, shock, cardiac arrhythmias, bleeding disorders, ptyalism, nausea, vomiting, respiratory distress, mental confusion, rhabdomyolysis, and acute renal failure (Ananda et al., 2009).